Quality, dissonance and rhythm within higher education - Waghid, Y. (South African Journal of Higher Education, 2019)
In this article, I argue for a position of quality in higher education commensurate with the cultivation of dissonance and rhythmic action. I focus specifically on the (South) African university and the reason why dissonance and rhythm offer pragmatic ways to respond to changes in and about university education. Without being oblivious of the tremendous strides universities have made on the African continent, my contention is that not enough has been done to ensure that quality and change have been enhanced. My argument is deconstructive and conceptual in the sense that I endeavour to imagine what universities will look like beyond merely consolidating their claims of rationality. In this article, I offer my thoughts on new imaginings for higher education as propositional pieces cohered by the central themes of dissonance and rhythm.